Marriage Markets and the Rise of Dowry in India - Gaurav Chiplunkar; Jeffrey Weaver (Institute of Labor Economics (IZA), 2023)
Dowry payments are common in many marriage markets. This paper uses data on over 74,000 marriages in rural India over the last century to explain why the institution of dowry emerges and how it evolves over time. We find that the proportion of Indian marriages including dowry payments doubled between 1930 and 1975, and the average real value of payments tripled. We empirically test whether four prominent theories of dowry can explain this rise, and find support for only one: increased differentiation in groom quality as a result of modernization. We also find a decline in the average real value of dowry payments after 1975 and demonstrate that this could be rationalized within a search model of marriage markets.
Keywords: J12; N35; O15; 330; dowry; marriage markets; India